Pelatihan Mendesain Pembelajaran Daring Menarik Selama Pandemi Covid-19 dengan Teknologi Pembelajaran Sederhana - Adaninggar Septi Subekti; Lemmuela Alvita Kurniawati (Dinamisia, 2020)
This community service was carried out to provide assistance to the situation experienced by English high school teachers in the sudden change of the learning modes due to the Covid-19 pandemic. It was conducted in the form of an online seminar on how to design interesting online learning by using simple instructional technology and how to combine asynchronous and synchronous learning modes. The 150-minute-online seminar was held on the Zoom platform and YouTube livestreaming. The session was divided into three main parts, namely 1) introduction of the 5E framework for online learning, 2) examples of material design using simple instructional technology, and 3) examples of simple instructional technology. In general, it can be concluded that this community service not only provided an introduction and understanding of online learning design with simple instructional technology, but also enhanced the participants' pedagogical knowledge of online learning design.